Trends in the development of the initiative budgeting in the regions of the Far Eastern federal district - K. I. Galynis (Вестник университета, 2019)
The theoretical review of research in the field of initiative budgeting in Russia has been presented. It has been concluded at the moment, that the theoretical basis of this mechanism, that allows to involve resident population in solving the problems of the territory is developed and discussed. Quite unique tools of initiative budgeting have been considered during analysis practice of initiative budgeting in Far Eastern Federal District. These tools can be implemented along with the classical methods of initiative budgeting (for instance the local initiatives support program) in other regions.